Self-Assembled Polyaniline/Ti3C2Tx Nanocomposites for High-Performance Electrochromic Films - Tao Lin (MDPI AG, 2021)
Electrochromic materials and devices are attracting intense attention because of their low energy consumption and open-circuit memory effect. Considering the difficult processing characteristics of electrochromic conductive polymers, we developed a facile and scalable strategy to prepare solution processable polyaniline (PANI)-based nanocomposites by introducing two-dimensional titanium carbon nanosheets (MXene) through a self-assembly approach. The PANI/MXene nanocomposite can be fabricated into porous films via spray-coating process, which show an obvious synergetic effect of both materials, leading to superior electrochromic properties. The optical contrast of the optimized PANI/MXene film reached as high as 55% at =700 nm, and its response times were 1.3 s for coloration and 2.0 s for bleaching, respectively. In addition, the composite film also showed excellent cycle stability (after 500 cycles, the ΔT retention was above 87%). The improved electrochromic properties are owed to the high conductivity of MXene and the formation of the porous composite film structure, which promote the electronic/ionic transfer and migration efficiency. This research suggests that the self-assembly method and the conductive polymer/MXene nanocomposites have a potential application in the fields of electronic functional films and devices.